Additional file 2 of “Mapping suicide prevention initiatives targeting Indigenous Sámi in Nordic countries” - Jon Petter A. Stoor (11659510); Heidi A. Eriksen (7778270); Anne C. Silviken (11659513) (2021)
Additional file 2: Supplementary Table 2. Descriptive characteristics of suicide prevention initiatives targeting Sámi in Norway, Finland and internationally.